1998
DOI: 10.1007/s004320050130
|View full text |Cite
|
Sign up to set email alerts
|

Do metallothioneins affect the response to treatment in testis cancers?

Abstract: In patients with germ cell testicular tumors, high MT expression, as detected by immunohistochemistry, predicts a better response rate to chemotherapy whereas tumors lacking or demonstrating low MT expression show a worse prognosis. These data do not support the hypothesis that MT overexpression contributes to cisplatinum resistance, at least in this tumor type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
2
10
0
1
Order By: Relevance
“…In our study, however, MT-protein expression certainly did not differ between primary germ-cell tumours of responding and of non-responding patients. Data on MT-protein expression in patients with disseminated non-seminoma in the mentioned studies (15, 31 and 14 patients in studies by Chin et al (1993) and Eid et al (1998) and in the present study respectively) are, as far as evaluable, still comparable. Overall, MT-protein over-expression is found in at least 85% of the tumours of responding patients.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…In our study, however, MT-protein expression certainly did not differ between primary germ-cell tumours of responding and of non-responding patients. Data on MT-protein expression in patients with disseminated non-seminoma in the mentioned studies (15, 31 and 14 patients in studies by Chin et al (1993) and Eid et al (1998) and in the present study respectively) are, as far as evaluable, still comparable. Overall, MT-protein over-expression is found in at least 85% of the tumours of responding patients.…”
Section: Resultssupporting
confidence: 52%
“…In our study, no direct relation was observed between protein levels of MT and total p53. In ductal carcinoma in situ of the breast, MT and p53 expression, though both elevated, were not found to be correlated (Douglas-Jones et al, 1997), while Eid et al (1997Eid et al ( , 1998 reported that MT and p53 expression in germ-cell tumours was related. The functional significance of MT as distributor of essential co-factors (zinc/copper) clearly merits further study.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Using the meta-analysis, no association of MT staining and tumor stage was observed in bladder [44], [83], [107], endometrial [108], [109], testicular [6], [98], kidney [110], [111], and head and neck cancer [41], [51]. There are also studies regarding tumors of breast [45], liver [74], and stomach [43] showing no significant association between MT staining and the tumor stage (Table 2).…”
Section: Resultsmentioning
confidence: 97%
“…In a variety of human germ tumour cell lines, the increased MT expression observed was concomitant with increased cisplatin resistance 135,136 . In contrast, in patients with germ cell testicular tumours, high MT immunoreactivity was found to predict a better response rate to chemotherapy, opposing the hypothesis that MT overexpression contributes to cisplatin resistance in this tumour type 137 . Additionally, it is known that metastatic testicular germ cell tumours are cured in most cases using cisplatin‐based combination chemotherapy 138 .…”
Section: Testicular Neoplasiamentioning
confidence: 99%